Sensory analysis and physicochemical characteristics of carica [Vasconcellea pubescens] fruit leather with seaweed [Eucheuma cottonii] addition. Issue 1 (May 2021) - Sukotjo, S; Nurani, D; Juliansyah, M A
Abstract: Carica [ Vasconcellea pubescens ] is a type of papaya fruit mostly cultivated in the Dieng area, Central Java, Indonesia. Carica is smaller than regular papaya, has an orange to yellow color, the flesh is tough, has a lot of sap and the taste is a bit sour. One of the products that can be made from Carica is fruit leather. Fruit leather is the processed fruit puree in the form of a thin sheet with a thickness of 2-3 mm, resembles a skin, has a plastic texture, can be rolled, and has a distinctive fruit flavor. The seaweed [ Eucheuma cottonii ] which mostly contains carrageenan, is added in the process to give the elastic texture to the fruit leather. The purposes of this study are to compare the effect of seaweed concentration on Carica fruit preferred by panelists and to analyze the physicochemical characteristics of the fruit leather. The process of making Carica fruit leather is done by preparing Carica puree, adding sugar, adding seaweed, heating, molding, and drying. The statistical analysis shows no effect of seaweed concentration on the panelists' preference test. The product has a sweet and slightly sour taste, yellowish to light brown color with the aroma of Carica. The physical analysis shows that the fruit leather has a thickness of 1.8-2.0 mm, a chewy texture, and a yield of 22.46-27.21%. Chemical analysis shows that the water content is 22.18-25.31%, the vitamin C content is 0.94-1.69 mg/100g, and dietary fiber is 5.19-10.31%.